Pengaruh Instagram terhadap Keputusan Menginap Milenial di The Apurva Kempinski Bali - Suryajaya, I Gede Octa; Febianti, Febianti; Rinayanthi, Ni Made (Penerbit Goodwood, 2024)
Purpose: This study aims to determine the effect of social media on Instagram on the decision to stay. The population uses the millennial generation who decide to stay at The Apurva Kempinski Bali and read information on Instagram about The Apurva Kempinski Bali and a sample of 100 respondents. Research methodology: The data collection method used a questionnaire. The data analysis technique used validity test, reliability test, classical assumption test, multiple linear regression analysis, determination coefficient test, and t-test. From the results of the study, the results obtained were that social media had a significant effect on the decision to stay, it is expected to provide good service and provide complete facilities, so that later consumers will give a good assessment on The Apurva Kempinski Bali's Instagram.Results: The research shows that Instagram social media has a positive and significant influence on millennials' stay decisions at The Apurva Kempinski Bali. This is in line with previous findings which show that the use of Instagram can influence guests' preferences and attraction to stay at certain hotels. Attractive and interactive visual content on Instagram can increase millennials' interest and decision to stay.Conclusions: Instagram social media has a positive and significant influence on millennials’ decision to stay at The Apurva Kempinski Bali. Interesting and interactive visual content on Instagram can increase interest and decision to stay. An effective digital marketing strategy through platforms such as Instagram is essential to attract millennials.Limitations: This study is limited to one location, namely The Apurva Kempinski Bali, so the results may not be generalizable to other hotels with different characteristics.Contribution: This research makes an important contribution in strengthening the understanding of the strategic role of social media, particularly Instagram, in influencing millennials' stay decisions in the hospitality industry. The finding that engaging and interactive visual content can significantly increase interest and stay decisions shows that social media management is not only a promotional tool, but also a determining factor in shaping consumer preferences.Keywords: Decision to Stay, Social MediaHow to Cite: Suryajaya, I, G, O. Febianti, F. Rinayanthi, N, M. (2024). Pengaruh Media Sosial Instagram terhadap Keputusan Menginap Generasi Milenial di The Apurva Kempinski Bali. Jurnal Studi Perhotelan dan Pariwisata, 2(2), 107-113.